678. Title: Treatment Outcomes with Carbapenems vs. Non-Carbapenem Beta-Lactams in Infections with Carbapenem-Discordant Enterobacter cloacae Complex. (15th December 2022) - Spence, Matthew; Mason, Matt; Wilson, Nicole; Liesman, Rachael
Abstract: Background: Carbapenem-discordant Enterobacter cloacae complex (CDECC) isolates are defined as ertapenem non-susceptible and meropenem susceptible drug phenotype. The optimal treatment of these infections is unknown. In 2021, the Infectious Diseases Society of America released guidance recommending extended infusion meropenem as the preferred treatment option. Newer agents, including ceftazidime-avibactam, may be effective but comparative data is lacking. Evaluation of treatment outcomes for use in infections with CDECC is necessary to establish optimal therapy. Methods: This single center, retrospective, cohort study was conducted at The University of Kansas Hospital from January 2016 to June 2021. Individuals at least 18 years of age with non-urinary culture positive for CDECC that were treated with either meropenem (MEM) or a non-carbapenem beta-lactam (NCBL) were included. Individuals with polymicrobial infections, infections from a urinary source, or death within 72 hours of admission were excluded. The primary outcome was clinical failure, which was a composite endpoint. Secondary outcomes included individual components of the primary outcome. Results: There were 29 unique episodes of monomicrobial, carbapenem-discordant Enterobacter cloacae complex infections during the study period. The primary outcome was met in 6 patients receiving a NCBL and 6 patients receiving MEM, respectively (67% vs. 30%, p=0.11). A total of 8 patients died within 30 days, 4 in the MEM group and 4 in the NCBL group (20% vs. 44%, p = 0.21). Univariate logistic regression analysis demonstrated a significant increase in need to modify antibiotic therapy in the NCBL group (OR 15.2, 95% CI, 1.37-168; p=0.02), with a trend towards increased risk for in-hospital 30-day mortality (OR, 3.2; 95% CI, 0.58-17.72; p = 0.18). Conclusion: There was no difference in clinical failure rates between the MEM and NCBL treatment groups. However, treatment with NCBLs was associated with a trend towards increased in-hospital mortality and need for antibiotic modifications due to clinical decompensation. Larger studies are needed to assess treatment outcomes in carbapenem-discordant Enterobacter cloacae complex infections to define optimal antibiotic therapy. Disclosures: All Authors : No reported disclosures.